The association of miR-126-3p, miR-126-5p and miR-664-3p expression profiles with outcomes of patients with metastatic colorectal cancer treated with bevacizumab - Ondrej Fiala; Pavel Pitule; Petr Hosek; Vaclav Liska; Ondrej Sorejs; Jan Bruha; Ondrej Vycital; Tomas Buchler; Alexandr Poprach; Ondrej Topolcan; Jindrich Finek (Tumor Biology, 2017)
MicroRNAs regulate the expression of genes involved in several important cancer-related processes including cell adhesion, proliferation, and tumour angiogenesis. Bevacizumab is routinely used in the treatment of patients with metastatic colorectal cancer, but, so far, no reliable biomarker predicting response to bevacizumab has been established. The aim of our retrospective study was to evaluate the association of miR-126-3p, miR-126-5p and miR-664-3p tumour expression levels with outcomes of patients with metastatic colorectal cancer treated with bevacizumab. The study included 63 patients. For the assessment of microRNA expression, gene-specific TaqMan assays were used. The median progression-free survival and overall survival for patients with low tumour expression of miR-126-3p were 8.8 and 20.6 months versus 13.5 months and median overall survival was not reached for patients with high expression ( p  = 0.0064 and p  = 0.0027), respectively. The median progression-free survival and overall survival for patients with low tumour expression of miR-126-5p were 9.0 and 22.2 months versus 12.0 and 23.4 months for patients with high expression ( p  = 0.2113 and 0.6858), respectively. The median progression-free survival and overall survival for patients with low tumour expression of miR-664-3p were 9.1 and 22.5 months versus 8.8 and 23.4 months for patients with high expression ( p  = 0.2542 and p  = 0.1922), respectively. The multivariable Cox proportional hazards model revealed that miR-126-3p expression was significantly associated with progression-free survival (hazard ratio = 0.28, p  = 0.0053) and also with overall survival (hazard ratio = 0.18, p  = 0.0046). In conclusion, the results of this study suggest that the expression of miR-126-3p in the tumour tissue was associated with outcome of metastatic colorectal cancer patients treated with bevacizumab.